(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
Untranslatability is a problem facing those who are involved in the translation studies then and ever. Meanwhile, it is still debatable whether translation is a skillful art or an independent science. Translation is divided into technical and literary. The first was agreed upon that it is accurate while the latter is still being involved in another debate to the extent that some theorists believe in the untranslatability; which means that translation is limited and cannot transfer all kinds of literary texts. The present research paper classifies the phenomenon of untranslatability into three categories each of which will be illustrated through clear examples, from some masterpieces of literature to poetic examples reaching sacred texts. The purpose of this study is to show the lack of an overall theory that might cover these specific texts and send readers back to read the source text - wherever the untranslatability is there - to fully and perfectly understand the meaning, and it will urge authors, poets and professionals to learn source languages in order to deeply understand the source texts. KEYWORDS- Untranslatability, Challenge, Literary Translation, English/ Arabic Source Texts.